Conceptual Framework and Hypotheses - Pender, John L.; Place, Frank; Ehui, Simeon (International Food Policy Research Institute, 2006)
In this chapter we introduce the conceptual framework that underlies the case studies presented in this book and discuss hypotheses about the effects of key factors on community and household decisions concerning income strategies and land management. We also discuss the influence of such decisions on outcomes such as agricultural production, household income, and land degradation (or improvement). This chapter is adapted from Scherr et al. (1996); Pender, Place, and Ehui (1999); Pender, Scherr, and Durón (2001); and Nkonya et al. (2004). The conceptual framework considers the effects of dynamic driving forces of change, such as population growth and changes in access to technology, markets, infrastructure, and services, as well as of more slowly changing conditioning factors such as agricultural potential, local institutions, and culture. We also consider the influence of government policies, programs, and institutions, which may influence income strategies, land management, and outcomes in many ways at different levels by affecting the driving forces and conditioning factors at the local level, by directly promoting or inhibiting different income strategies and land management practices, or by directly affecting outcomes (e.g., through food aid). We argue that the impacts of many factors are likely to be context-dependent, emphasizing the importance of empirical research in specific contexts, though some unambiguous hypotheses are derived. In general, policy and program interventions are likely to involve tradeoffs among the objectives of increasing agricultural productivity, increasing household income, and reducing land degradation.